Dan Hong Injection Protects Against Cardiomyocytes Apoptosis by Maintaining Mitochondrial Integrity Through Keap1/Nuclear Factor Erythroid 2-Related Factor 2/JNK Pathway - Zhang, Ling; Wang, Yu; Li, Chang; Shao, Chongyu; Zhou, Huifen; Yang, Jiehong; He, Yu; Wan, Haitong (Frontiers in Pharmacology, 2020)
Danhong injection (DHI) is used widely against cardiovascular disease in China. Recent studies have demonstrated its mitochondria-protection effect as being pivotal in treatment of myocardial ischemia/reperfusion (I/R) injury, but the underlying mechanism of action is incompletely understood. We aimed to identify the effect and mechanism of action of DHI on mitochondrial integrity and cardiomyocyte apoptosis after I/R. An I/R rat model was induced to detect the effect of DHI on myocardial repair by infarct size, apoptosis and oxidative stress. In vitro, H9C2 cells or H9C2 cells with nuclear factor erythroid 2-related factor 2 (Nrf2) knockdown were injured under hypoxia-reoxygenation (H/R). The effects of DHI on apoptosis, antioxidant capacity and mitochondrial integrity were evaluated by mitochondrial morphology, apoptosis rate, reactive oxygen species (ROS) generation, adenosine triphosphate (ATP) levels, mitochondrial membrane potential, and oxygen consumption in H9C2 cells treated with H/R. The underlying mechanism of action of DHI in maintenance of mitochondrial integrity and anti-apoptosis was detected in H9C2 cells with or without Nrf2 knockdown. DHI treatment significantly decreased the infarct size, inhibited apoptosis and suppressed oxidative stress in the hearts of I/R rats. Also, DHI promoted cell survival by: an anti-apoptosis action; inhibiting ROS generation; maintaining mitochondrial morphology with increased mitochondrial length; alleviating mitochondrial dysfunction with a decreased mitochondrial membrane potential; increasing ATP levels and the oxygen-consumption rate. Moreover, the Keap1/Nrf2/JNK pathway was found to be involved in DHI reducing oxidative stress and maintaining mitochondrial integrity. We revealed a novel mechanism by which DHI protected H9C2 cells against H/R injury via the Keap1/Nrf2/JNK pathway and provided a mitochondrial protectant for the treatment of myocardial I/R injury.